1985
DOI: 10.1111/j.1476-5381.1985.tb08916.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the histamine H2‐receptor mediating relaxation of the parenchymal lung strip preparation of the guinea‐pig

Abstract: The relaxation produced by several H2-receptor agonists and forskolin was investigated on strips of guinea-pig lung parenchyma. Dimparit, 1 microM to 10 mM, 4-methyl histamine, 0.5 microM to 100 microM and impromidine, 10 nM to 1 microM, had no effect on the tone of the unstimulated strips of lung parenchyma but caused a dose-dependent relaxation of strips that were contracted by 2-pyridylethylamine (2-PEA), 15 microM. Forskolin, 10 nM to 4 microM, produced a dose-dependent relaxation of both the stimulated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 31 publications
5
12
1
1
Order By: Relevance
“…Ranitidine has previously been shown to be 4 to 10 times more potent than cimetidine at the H2-receptor (Bradshaw et al, 1979) but the lung and cerebral cortex studies shown in Table 2 In conjunction with the preceding paper (Foreman et al, 1985) we have demonstrated an H2-receptor by binding studies whose interaction with agonists and antagonists quantitatively matches the pharmacological potencies of these drugs on the contractile responses of the lung strip.…”
Section: Kinetics Of [3h]-tiotidine Bindingsupporting
confidence: 57%
See 1 more Smart Citation
“…Ranitidine has previously been shown to be 4 to 10 times more potent than cimetidine at the H2-receptor (Bradshaw et al, 1979) but the lung and cerebral cortex studies shown in Table 2 In conjunction with the preceding paper (Foreman et al, 1985) we have demonstrated an H2-receptor by binding studies whose interaction with agonists and antagonists quantitatively matches the pharmacological potencies of these drugs on the contractile responses of the lung strip.…”
Section: Kinetics Of [3h]-tiotidine Bindingsupporting
confidence: 57%
“…We have compared the inhibition constants obained in this study for a variety of H2-compounds, with KB values calculated from inhibition of the action of dimaprit in lung parenchyma reported in the preceding paper (Foreman et al, 1985) and from the inhibition of the chronotropic activity of histamine in guinea-pig right atria (Table 2). For the H2-antagonists there is a correlation between the inhibition constants obtained in the present study and the dissociation constants obtained in both the isolated lung strip and the right atria (r = 0.97, P < 0.01 and r = 0.95, P < 0.01 respectively).…”
Section: Kinetics Of [3h]-tiotidine Bindingmentioning
confidence: 99%
“…Whereas early studies in guinea pig brain, lung, and transfected CHO cells have been successful using [ 3 H]tiotidine (cf. 31) (Gajtkowski et al, 1983;Norris et al, 1984;Foreman et al, 1985;Gantz et al, 1991b), studies in rat brain and guinea pig mucosal cells were not successful (Maayani et al, 1982;Batzri and Harmon, 1986). The introduction of […”
Section: Anatomic Frameworkmentioning
confidence: 99%
“…H1 receptors are coupled to inositol phosphate hydrolysis and mediate a variety of responses, including smooth muscle contraction, increased vascular permeability and hormone release (Hill, 1990). H2-receptors are coupled to adenylate cyclase via a G.-protein and the functional H2-responses include smooth muscle relaxation and inhibition of the immune system (Foreman et al, 1985). H3-receptors were originally recognized in rat brain where they appeared to be involved in the feedback control of both histamine synthesis and release (Arrang et al, 1987).…”
Section: Introductionmentioning
confidence: 99%